Assessment of population coverage of hypertension screening in Thailand based on the effective coverage framework - Kulpimol Charoendee; Jiruth Sriratanaban; Wichai Aekplakorn; Piya Hanvoravongchai (BMC, 2018)
Abstract Background Hypertension (HT) is a major risk factor, and accessible and effective HT screening services are necessary. The effective coverage framework is an assessment tool that can be used to assess health service performance by considering target population who need and receive quality service. The aim of this study is to measure effective coverage of hypertension screening services at the provincial level in Thailand. Methods Over 40 million individual health service records in 2013 were acquired. Data on blood pressure measurement, risk assessment, HT diagnosis and follow up were analyzed. The effectiveness of the services was assessed based on a set of quality criteria for pre-HT, suspected HT, and confirmed HT cases. Effective coverage of HT services for all non-HT Thai population aged 15 or over was estimated for each province and for all Thailand. Results Population coverage of HT screening is 54.6%, varying significantly across provinces. Among those screened, 28.9% were considered pre-HT, and another 6.0% were suspected HT cases. The average provincial effective coverage was at 49.9%. Around four-fifths (82.6%) of the pre-HT group received HT and Cardiovascular diseases (CVD) risk assessment. Among the suspected HT cases, less than half (38.0%) got a follow-up blood pressure measurement within 60 days from the screening date. Around 9.2% of the suspected cases were diagnosed as having HT, and only one-third of them (36.5%) received treatment within 6 months. Within this group, 21.8% obtained CVD risk assessment, and half of them had their blood pressure under control (50.8%) with less than 1 % (0.7%) of them managed to get the CVD risk reduced. Conclusions Our findings suggest that hypertension screening coverage, post-screening service quality, and effective coverage of HT screening in Thailand were still low and they vary greatly across provinces. It is imperative that service coverage and its effectiveness are assessed, and both need improvement. Despite some limitations, measurement of effective coverage could be done with existing data, and it can serve as a useful tool for performance measurement of public health services.